Guyton and Hall textbook of medical physiology - Hall, John E. (John Edward), 1946-; Hall, Michael E. (Michael Edward) (New Delhi : Elsevier, 2021)
"This is a comprehensive textbook of medical physiology"--
Revised edition of: Guyton and Hall textbook of medical physiology / John E. Hall. 13th edition. [2016].
Includes bibliographical references and index.
PHR
Book Finder International
Keywords: Human physiology; Physiology, Pathological; Pharmacy